Zwitterionic functionalized cyclodextrin sulfonated polymer proton exchange membrane and preparation method thereof
By introducing zwitterion-functionalized cyclodextrin (ZCD) into the proton exchange membrane, the problem of insufficient proton conductivity of the existing proton exchange membrane is solved, and the significant improvement of proton conductivity and optimization of membrane performance is achieved.
Patent Information
- Application Number
- CN202411235134.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The proton conductivity of existing proton exchange membrane fuel cells is insufficient, which affects its performance and expansion of application fields.
The sulfonated polymeric substances' union-functionalized cyclodextrin (ZCD) is introduced to modify the sulfonated polymeric substances to improve its proton conductivity. The specific method includes synthesizing the zwitterionic compound AEPPS and grafting it onto the cyclodextrin to obtain ZCD, and then doping it into the sulfonated polymer to form a modified proton exchange membrane.
The proton conductivity of the proton exchange membrane is significantly improved, especially under high temperature conditions, the proton conductivity of the modified membrane can reach several times the unmodified, improving the stability and durability of the membrane.
Smart Images

Figure CN119708578A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of membrane technology, and more specifically, relates to a zwitterion functionalized cyclodextrin sulfonated polymer proton exchange membrane and a preparation method thereof. By introducing zwitterion functionalized cyclodextrin (ZCD) to modify the sulfonated polymer proton exchange membrane, the proton conductivity of the prepared proton exchange membrane can be effectively improved. Background Art
[0002] Fuel cell technology has attracted much attention for its high efficiency and the green and safe characteristics of its reaction products. Among them, proton exchange membrane fuel cells (PEMFC) have been widely used in portable power sources and new energy vehicles due to their advantages such as high energy conversion rate, high power density, and fast startup speed. They are considered to be one of the most promising fuel cells. As a key component of proton exchange membrane fuel cells, proton exchange membrane (PEM) not only provides a channel for proton transmission, but also blocks the fuel between the positive and negative electrodes. Among them, proton conductivity is a core factor that determines the performance of proton exchange membrane fuel cells. Improving proton conductivity is an effective way to obtain high-performance proton exchange membranes.
[0003] Zwitterionic materials are a type of material with remarkable superhydrophilicity, benefiting from their equivalent anionic and cationic functional groups on a neutral molecule. Compared with nonionic materials, zwitterionic materials have significantly stronger hydration properties than nonionic materials. In proton exchange membrane modification, zwitterions can bind to ion exchange sites in proton exchange membranes through ion exchange, thereby improving proton conductivity, as well as membrane stability, durability and selectivity. n-Aminoethylpiperazine propane sulfonate (AEPPS) has attracted attention among zwitterionic materials due to its strong water binding ability and mild and simple synthesis method. It has been reported in membrane modification. "Separation and Purification Technology" (Separation and Purification Technology, 2022, 285: 120298) co-deposited tannic acid (TA) and AEPPS on the surface of the prepared polyvinylidene fluoride (PVDF) / poly(2-hydroxyethyl methacrylate) (PVDF / PHEMA) composite membrane, and the double anionic surface has excellent underwater anti-oil adhesion ability. Journal of Membrane Science (2022, 643: 120050) used low concentrations of N-aminoethylpiperazine propane sulfonate (AEPPS) as an aqueous monomer to prepare a membrane with excellent nanofiltration performance. Journal of Membrane Science (2016, 510: 122-130) prepared a super-hydrophilic antibacterial zwitterionic polyamide thin film composite nanofiltration membrane (ZTFCMs) with excellent water permeability and antibiotic selectivity by interfacial polymerization of AEPPS monomer and trimesoyl chloride (TMC) monomer on polysulfone ultrafiltration. However, the application of zwitterionic compound AEPPS in improving proton conductivity has not been reported yet, so its application in modified proton exchange membranes has certain research value.
[0004] β-cyclodextrin (β-CD) is an organic compound composed of D-pyranose glucose units connected in a ring by α-1,4-glycosidic bonds. Cyclodextrin has a hole in the center of the ring structure, with -CH- oxygen atoms bound to glucoside inside, which is hydrophobic. Meanwhile, the -OH groups at the 2nd, 3rd and 6th positions of glucose are hydrophilic, making it an organic compound that is easy to be functionalized with zwitterions (Chemical Reviews, 2014, 114(21): 10940–10975). At the same time, the hydroxyl groups on the surface of β-CD can provide more proton conductivity channels. Therefore, more and more β-CD-modified proton exchange membranes have been developed. For example, the Journal of Power Sources (2008, 185, 1, 49-54) prepared H-based sodium ions by solution casting. +The proton conductivity of the proton conductive composite membrane based on sb-CD was 0.0144S / cm at 20°C, which was higher than that of the unmodified membrane (0.0105S / cm). The International Journal of Hydrogen Energy (2011, 36, 9, 5666-5674) prepared and studied the DMFC blend membrane with sulfonated polyetheretherketone and sulfonated cyclodextrin as the proton conductive membrane. The conductivity of the membrane was up to 0.057S / cm at 80°C, which was significantly higher than that of Nafion115 (0.034S / cm). Electrochimica Acta (2018, 286, 350e364) reported that a composite membrane was successfully developed by adding sulfonated β-CD to TGDMP cross-linked sulfonated PVA. The proton conductivity of the membrane was 0.143S / cm at 80°C and 100% RH (relative humidity), which was significantly improved compared with the unmodified sulfonated poly (vinyl alcohol) membrane. Polymer Testing (2021, 100, 107246) reported that a SPEEK / β-CD-DHNTs / HPW composite membrane was prepared by anchoring phosphotungstic acid with β-cyclodextrin. At 25°C and 90% RH, the conductivity of the composite membrane was as high as 0.090S / cm, which was about 120% higher than that of the SPEEK membrane (0.041S / cm). Journal of Materials Chemistry A (2015, 30, 3, 15607-15615) reported that silica nanoparticles (SNs) were modified with β-CD, and then SN-β-CD was mixed into Nafion membrane. The proton conductivity of the proton exchange membrane was as high as 0.31S / cm at 80°C and 100% RH, which is almost 3 times that of the unmodified membrane. Although the proton conductivity of these β-CD modified membranes has been improved, the improved proton conductivity is not high enough. Although a few have a good improvement, they are still difficult to industrialize due to the complex preparation. There is still a lot of room for improvement. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the object of the present invention is to provide a zwitterion-functionalized cyclodextrin sulfonated polymer proton exchange membrane and a preparation method thereof, wherein the proton conductivity of the prepared proton exchange membrane can be effectively improved by improving the structure and composition of the key functional components in the proton exchange membrane, modifying the sulfonated polymer proton exchange membrane by introducing zwitterion-functionalized cyclodextrin (ZCD), and controlling the overall process design of the preparation method.
[0006] To achieve the above object, according to one aspect of the present invention, a method for preparing a zwitterion functionalized cyclodextrin sulfonated polymer proton exchange membrane is provided, characterized in that it comprises the following steps:
[0007] (1) N-aminoethylpiperazine (AEP) and a first solvent are placed in a container together, and then a mixture of 1,3-propyl sultone (1,3-PS) and a second solvent is added dropwise to the container under a water bath condition of 20° C. to 50° C., and the mixture is stirred for reaction, and then the product is separated, washed, and dried to obtain a corresponding zwitterionic compound, which is recorded as AEPPS;
[0008] (2) AEPPS obtained in step (1) is stirred together with a soluble strong base compound (i.e., NaOH), β-cyclodextrin (β-CD), and deionized water in an oil bath at 60° C. to 100° C., and epichlorohydrin (ECH) is added dropwise thereto to obtain a mixed solution, which is then connected to a reflux condenser for heating and reflux reaction, and the product is then separated, washed, and dried to obtain the corresponding zwitterionic compound-modified cyclodextrin, which is recorded as ZCD;
[0009] (3) dispersing the ZCD obtained in step (2) in a sulfonated polymer solution, and ultrasonically treating the solution to obtain a uniformly dispersed casting solution; then, using the casting solution to form a membrane material, drying the membrane material, and then sequentially soaking the membrane material in a hydrogen peroxide solution, an acid, and deionized water to obtain a zwitterion-functionalized cyclodextrin sulfonated polymer proton exchange membrane.
[0010] As a further preferred embodiment of the present invention, in step (2), the dropwise added volume of epichlorohydrin accounts for 5 to 20% of the total volume of the mixed solution; the reaction temperature of the reflux heating reaction is 60 to 80° C., and the reaction time is 15 to 180 min;
[0011] Preferably, the dropwise added volume of epichlorohydrin accounts for 5-12% of the total volume of the mixed solution; the reaction temperature of the reflux heating reaction is 65-80° C., and the reaction time is 15-150 min.
[0012] As a further preferred embodiment of the present invention, in step (3), the mass of ZCD accounts for 0.7-2.1 wt % of the mass of the polymer matrix contained in the sulfonated polymer solution.
[0013] As a further preferred embodiment of the present invention, in step (1), the molar ratio of the N-aminoethylpiperazine to the 1,3-propyl sultone corresponding to the stirring reaction is 5:1 to 1:5.
[0014] As a further preferred embodiment of the present invention, in step (1), the first solvent and the second solvent are independently selected from one or a mixture of N,N-dimethylformamide (DMF), acetonitrile, N,N-diethylformamide, tetrahydrofuran, pyrrolidone, dimethyl sulfoxide, CH3OH, C2H5OH;
[0015] The temperature of the water bath condition is 25-45° C.; the reaction time of the stirring reaction is 2-12 hours.
[0016] As a further preference of the present invention, in step (1) and step (2), the solvents used for cleaning are all low-boiling-point solvents having a boiling point not higher than 80°C, independently selected from one or a mixture of CH3OH, C2H5OH, CHCl3, CH2Cl2, CH3Cl, acetone, butanone.
[0017] As a further preferred embodiment of the present invention, in step (3), the sulfonated polymer solution is a homogeneous solution of perfluorosulfonic acid resin, sulfonated polyetheretherketone, sulfonated polybenzimidazole, sulfonated polyethersulfone or sulfonated polyimide; the concentration of the sulfonated polymer solution is 1 to 40 wt%;
[0018] Using the casting liquid to form a membrane material, specifically coating the casting liquid to form a membrane;
[0019] The drying is to place the membrane material in an oven at 50-80°C, heat it to 110-150°C, and then keep it for 12-36 hours; preferably, the heating rate of the heating is less than 0.5°C / min, more preferably 0.1-0.5°C / min.
[0020] As a further preferred embodiment of the present invention, in step (3), the concentration of the hydrogen peroxide solution is 1 to 10 wt %;
[0021] The acid solution is specifically one or a mixture of hydrochloric acid, sulfuric acid, phosphoric acid, and the concentration of the acid solution is 0.1 to 2 mol / L, more preferably 0.5 to 2 mol / L.
[0022] According to another aspect of the present invention, the present invention provides a zwitterion functionalized cyclodextrin sulfonated polymer proton exchange membrane prepared by the above preparation method.
[0023] According to another aspect of the present invention, the present invention provides the use of the above zwitterion functionalized cyclodextrin sulfonated polymer proton exchange membrane in a proton exchange membrane fuel cell.
[0024] Compared with the prior art, the above technical solutions conceived by the present invention can achieve the following
[0025] Beneficial effects:
[0026] (1) Through the above technical scheme conceived by the present invention, unlike the traditional polymer hybrid proton exchange membrane modified by other materials, the AEPPS used in the present invention contains sulfonic acid groups and ammonium cations, has amphiphilicity, and can show good application potential in the field of proton exchange membrane fuel cells. The unique annular cavity structure of β-CD itself can reduce the proton conductive steric hindrance. In addition, β-CD stands out because of its wide source, low raw material price and simple construction process. The present invention selects β-CD and synthetic AEPPS to construct a composite proton exchange membrane. Taking the application of Nafion membrane as an example, using it as a filler can effectively improve the water retention of Nafion membrane, thereby improving its proton conductivity performance under high temperature conditions. It is crucial to the performance of energy conversion equipment such as fuel cells.
[0027] The research group of the inventor of the present invention reported a polymer hybrid proton exchange membrane with zwitterion functionalized COF and SiO2 spheres synergistically modified (see Chinese patent application CN117380003A). Although it can have a certain effect on accelerating proton conduction, it uses inorganic filler SiO2, which has poor compatibility with the matrix material, affecting the mechanical properties and service life of the membrane; at the same time, the preparation conditions of zwitterion functionalized COF are harsh, and the cost of carbon tube materials is high, which limits its promotion and application in practical applications. The present invention uses zwitterionized β-cyclodextrin (ZCD) as a filler, which has good compatibility with the matrix material, and the raw material β-CD used has a wide source and low preparation cost. At the same time, because of different proton transfer mechanisms, it can maintain good proton conductivity, so it has more application potential.
[0028] (2) Compared with the traditional cyclodextrin-modified polymer hybrid proton exchange membrane, zwitterionized β-cyclodextrin (ZCD) has better hydrophilicity and provides more proton transfer channels. In the microstructure of the proton exchange membrane, hydrated protons (H3O+) form continuous hydrogen bond paths through the electrostatic field of the sulfonic acid group, achieving efficient proton conduction. In addition to the sulfonic acid groups on the β-CD internal cavity modification that can open up a transmission path for proton transport, the sulfonic acid groups on the sulfonated polymer membrane can form hydrogen bonds with the quaternary ammonium ions on AEPPS, adding additional proton conduction sites, which can bind water molecules more strongly through electrostatic induction, further reducing the energy barrier for proton transfer from one site to another, thereby improving its proton conduction performance under high temperature conditions.
[0029] (3) Water molecules act as a solvating medium and together with sulfonic acid groups construct a stable transmission channel. Under high humidity, free water increases and widens the proton channel, promoting proton transition conduction. Therefore, the proton exchange membrane containing the zwitterionic compound AEPPS has good hydrophilicity, which can increase the content of water molecules in the membrane, promote the ionization of sulfonic acid groups to form proton clusters; as the water content increases, the clusters swell and link into continuous channels, significantly improving the proton conductivity. In particular, when applied to systems such as Nafion membranes, the advantages of AEPPS-modified β-CD modified proton exchange membranes are more significant. The introduction of ZCD significantly improves the stability and durability of the proton exchange membrane. Not only does it optimize the proton conduction mechanism, but it also significantly enhances the comprehensive performance of the modified proton exchange membrane, providing strong support for applications in fields such as proton exchange membrane fuel cells.
[0030] (4) Compared with the prior art, the preparation method of the present invention has a simple operation process, low production cost, mild preparation conditions, and is easy for large-scale production. The selected materials are biodegradable, meet the requirements of clean energy production, and have a good industrial production foundation and broad application prospects. At the same time, this study provides a forward-looking reference for the design and construction of proton exchange membranes with specific structures.
[0031] In summary, the present invention can obtain a proton exchange membrane with significantly improved proton conductivity through a simple process. The present invention obtains zwitterionized β-cyclodextrin (ZCD) by grafting AEPPS onto β-CD, which has good hydrophilicity. The zwitterionic groups thereon can provide additional proton conduction sites, which can bind water molecules more strongly through electrostatic induction, further reducing the energy barrier for proton transfer from one site to another. Using it as a filler can effectively improve the water retention of the membrane and greatly promote the conduction of protons in the proton exchange membrane. The obtained modified proton exchange membrane has good performance in both proton conduction and stability in use. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1The temperature-dependent proton conductivity comparison diagram (95% RH, RH: relative humidity) of the zwitterion-functionalized β-cyclodextrin (ZCD) hybrid proton exchange membrane (doping amount accounts for 0.7, 1.4 and 2.1 wt% of the mass of the Nafion matrix, respectively) obtained in Examples 1, 2 and 3 of the present invention and the unhybridized proton exchange membrane is shown. Among them, the legend "RN" represents an unhybridized proton exchange membrane; "ZCD / RN-0.7" represents a ZCD hybrid proton exchange membrane, and the ZCD doping amount accounts for 0.7 wt% of the mass of the Nafion matrix (i.e., the sample obtained in Example 1); "ZCD / RN-1.4" represents a ZCD hybrid proton exchange membrane, and the ZCD doping amount accounts for 1.4 wt% of the mass of the Nafion matrix (i.e., the sample obtained in Example 2); "ZCD / RN-2.1" represents a ZCD hybrid proton exchange membrane, and the ZCD doping amount accounts for 2.1 wt% of the mass of the Nafion matrix (i.e., the sample obtained in Example 3).
[0033] Figure 2 The figure is a comparison of the proton conductivity of β-CD and ZCD hybrid proton exchange membranes (the doping amount is 1.4wt% of the Nafion matrix mass) and unhybridized proton exchange membranes in temperature dependence (95% RH). Among them, the legend "RN" represents unhybridized proton exchange membranes; "β-CD / RN-1.4" represents β-CD hybridized proton exchange membranes, and the β-CD doping amount accounts for 1.4wt% of the Nafion matrix mass (i.e., the sample obtained in Comparative Example 1); "ZCD / RN-1.4" represents ZCD hybridized proton exchange membranes, and the ZCD doping amount accounts for 1.4wt% of the Nafion matrix mass (i.e., the sample obtained in Example 2).
[0034] Figure 3 This is a proton conductivity-time graph obtained from the proton conductivity stability test of ZCD / RN-1.4. "ZCD / RN-1.4" represents a ZCD hybrid proton exchange membrane, and the ZCD doping amount accounts for 1.4 wt% of the Nafion matrix mass (i.e., the sample obtained in Example 2). DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0036] The preparation method of the zwitterion functionalized cyclodextrin sulfonated polymer composite proton exchange membrane of the present invention generally comprises first preparing a zwitterion compound AEPPS, then grafting it onto cyclodextrin to obtain zwitterion functionalized β-cyclodextrin (ZCD), and finally doping it into a polymer to obtain a zwitterion functionalized cyclodextrin (ZCD) modified polymer hybrid proton exchange membrane, which may specifically include the following steps:
[0037] (1) N-aminoethylpiperazine (AEP) and 1,3-propyl sultone (1,3-PS) are mixed and stirred to synthesize a zwitterionic compound AEPPS;
[0038] (2) AEPPS and epichlorohydrin (ECH) were grafted onto cyclodextrin (β-CD) to obtain zwitterion-functionalized β-cyclodextrin (ZCD);
[0039] (3) Adding zwitterion-functionalized β-cyclodextrin (ZCD) to the sulfonated polymer solution to obtain a casting solution, thereby obtaining a zwitterion-functionalized cyclodextrin sulfonated polymer composite proton exchange membrane.
[0040] The following are specific embodiments:
[0041] Example 1
[0042] 1. AEP (7.22 g) and acetonitrile (65 ml) were placed in a 250 mL flask equipped with a stirring magnet, and then a mixture of 1,3-PS (5.9 g) and acetonitrile (5 mL) was slowly added dropwise to the flask in a 30°C water bath. The mixture was then stirred in a 30°C water bath for 6 h. After cooling, the pale yellow crude product was collected by centrifugation, thoroughly washed with acetone 5 times to remove unreacted monomers, and then vacuum dried at 50°C for 24 h to obtain the zwitterionic compound AEPPS.
[0043] 2. Prepare 30 mL of a mixed solution of 8 wt% NaOH and 14 wt% β-CD with deionized water, prepare 20 mL of a 14 wt% AEPPS aqueous solution, mix the two solutions in a 250 mL round-bottom flask equipped with a magnet, place the flask in an 80°C oil bath and stir, slowly add 4.4 mL of ECH, connect a reflux condenser, and continue to react at 80°C for 1 h. After cooling, centrifuge to remove the supernatant, wash with deionized water 5 times to remove unreacted monomers, and then vacuum dry at 30°C for 24 h to obtain zwitterionic compound-modified cyclodextrin ZCD.
[0044] 3. Accurately weigh ZCD at a ratio of 0.7wt%, dissolve it in 2mL DMF, and sonicate the solution for half an hour to ensure full dissolution. Take 4mL Nafion solution, remove the solvent by rotary evaporation at 43℃, and then add 2mL DMF to recast Nafion by rotary evaporation at 67℃. Then mix the corresponding ZCD solution with the recast Nafion solution and mix them evenly by ultrasonication for 3h. Slowly add the mixed solution to the preheated quartz mold, let it stand in a vacuum oven at 120℃ for 24h to remove the solvent, and obtain a composite proton exchange membrane with the corresponding ZCD content. Finally, the membrane is first soaked in 3wt% H2O2 solution at 80℃ for 1h, and then acidified with 1M H2SO4 at 80℃ for 1h to convert the membrane into H + The ZCD-modified proton exchange membrane was finally obtained.
[0045] The proton conductivity of the proton exchange membrane prepared in this example at 90° C. and 95% RH is as high as 0.189 S / cm, which is about 0.29 times higher than that of the unmodified proton exchange membrane (0.146 S / cm).
[0046] Example 2
[0047] 1. AEP (7.22 g) and acetonitrile (65 ml) were placed in a 250 mL flask equipped with a stirring magnet, and then a mixture of 1,3-PS (5.9 g) and acetonitrile (5 mL) was slowly added dropwise to the flask in a 30°C water bath. The mixture was then stirred in a 30°C water bath for 6 h. After cooling, the pale yellow crude product was collected by centrifugation, thoroughly washed with acetone 5 times to remove unreacted monomers, and then vacuum dried at 50°C for 24 h to obtain the zwitterionic compound AEPPS.
[0048] 2. Prepare 30 mL of a mixed solution of 8 wt% NaOH and 14 wt% β-CD with deionized water, prepare 20 mL of a 14 wt% AEPPS aqueous solution, mix the two solutions in a 250 mL round-bottom flask equipped with a magnet, place the flask in an 80°C oil bath and stir, slowly add 4.4 mL of ECH, connect a reflux condenser, and continue to react at 80°C for 1 h. After cooling, centrifuge to remove the supernatant, wash with deionized water 5 times to remove unreacted monomers, and then vacuum dry at 30°C for 24 h to obtain zwitterionic compound-modified cyclodextrin ZCD.
[0049] 3. Accurately weigh ZCD at a ratio of 1.4wt%, dissolve it in 2mL DMF, and sonicate the solution for half an hour to ensure full dissolution. Take 4mL Nafion solution, remove the solvent by rotary evaporation at 43℃, and then add 2mL DMF to recast Nafion by rotary evaporation at 67℃. Then mix the corresponding ZCD solution with the recast Nafion solution and mix them evenly by ultrasonication for 3h. Slowly add the mixed solution to the preheated quartz mold, let it stand in a vacuum oven at 120℃ for 24h to remove the solvent, and obtain a composite proton exchange membrane with the corresponding ZCD content. Finally, the membrane is first soaked in 3wt% H2O2 solution at 80℃ for 1h, and then acidified with 1M H2SO4 at 80℃ for 1h to convert the membrane into H + The ZCD-modified proton exchange membrane was finally obtained.
[0050] like Figure 2 As shown in FIG. 1 , the proton conductivity of the proton exchange membrane prepared in this embodiment at 90° C. and 95% RH is as high as 0.243 S / cm, which is about 0.66 times higher than that of the unmodified proton exchange membrane (0.146 S / cm). Figure 3 As shown, the proton conductivity hardly decreases when kept constant at 90°C and 95% RH for about 1020 min.
[0051] Example 3
[0052] 1. AEP (7.22 g) and acetonitrile (65 ml) were placed in a 250 mL flask equipped with a stirring magnet, and then a mixture of 1,3-PS (5.9 g) and acetonitrile (5 mL) was slowly added dropwise to the flask in a 30°C water bath. The mixture was then stirred in a 30°C water bath for 6 h. After cooling, the pale yellow crude product was collected by centrifugation, thoroughly washed with acetone 5 times to remove unreacted monomers, and then vacuum dried at 50°C for 24 h to obtain the zwitterionic compound AEPPS.
[0053] 2. Prepare 30 mL of a mixed solution of 8 wt% NaOH and 14 wt% β-CD with deionized water, prepare 20 mL of a 14 wt% AEPPS aqueous solution, mix the two solutions in a 250 mL round-bottom flask equipped with a magnet, place the flask in an 80°C oil bath and stir, slowly add 4.4 mL of ECH, connect a reflux condenser, and continue to react at 80°C for 1 h. After cooling, centrifuge to remove the supernatant, wash with deionized water 5 times to remove unreacted monomers, and then vacuum dry at 30°C for 24 h to obtain zwitterionic compound-modified cyclodextrin ZCD.
[0054] 3. Accurately weigh ZCD at a ratio of 2.1wt%, dissolve it in 2mL DMF, and sonicate the solution for half an hour to ensure full dissolution. Take 4mL Nafion solution, remove the solvent by rotary evaporation at 43℃, and then add 2mL DMF to recast Nafion by rotary evaporation at 67℃. Then mix the corresponding ZCD solution with the recast Nafion solution and mix them evenly by ultrasonication for 3h. Slowly add the mixed solution to the preheated quartz mold, let it stand in a vacuum oven at 120℃ for 24h to remove the solvent, and obtain a composite proton exchange membrane with the corresponding ZCD content. Finally, the membrane is first soaked in 3wt% H2O2 solution at 80℃ for 1h, and then acidified with 1M H2SO4 at 80℃ for 1h to convert the membrane into H + The ZCD-modified proton exchange membrane was finally obtained.
[0055] The proton conductivity of the proton exchange membrane prepared in this example at 90° C. and 95% RH is as high as 0.200 S / cm, which is about 0.36 times higher than that of the unmodified proton exchange membrane (0.146 S / cm).
[0056] Comparative Example 1
[0057] Accurately weigh β-CD at a ratio of 1.4wt%, dissolve it in 2mL DMF, and sonicate the solution for half an hour to ensure full dissolution. Take 4mL Nafion solution, remove the solvent by rotary evaporation at 43℃, and then add 2mL DMF to recast Nafion by rotary evaporation at 67℃. Then mix the corresponding ZCD solution with the recast Nafion solution and mix them evenly by ultrasonication for 3h. Slowly add the mixed solution to the preheated quartz mold, let it stand in a vacuum oven at 120℃ for 24h to remove the solvent, and obtain a composite proton exchange membrane with the corresponding ZCD content. Finally, the membrane is first soaked in 3wt% H2O2 solution at 80℃ for 1h, and then acidified with 1M H2SO4 at 80℃ for 1h to convert the membrane into H + The membrane was then washed with deionized water to obtain a β-CD modified proton exchange membrane.
[0058] The proton conductivity of the proton exchange membrane prepared in this comparative example at 90° C. and 95% RH is as high as 0.164 S / cm, which is about 0.12 times higher than that of the unmodified proton exchange membrane (0.146 S / cm).
[0059] The proton conductivity of the proton exchange membrane prepared in Comparative Example 1 at 90° C. and 95% RH is lower than that of the proton exchange membrane prepared in Example 2 at 90° C. and 95% RH, indicating the significant advantage of ZCD in improving the proton conductivity of proton exchange membranes.
[0060] The various raw materials used in the above embodiments are all commercially available. In addition, the proton conductivity detection conditions (temperature and humidity) in the above embodiments are only examples. Depending on the actual situation, the detection can also be performed under other temperature and / or humidity conditions. Generally, at higher humidity (greater than or equal to 90% RH), the proton conductivity increases with the increase of temperature.
[0061] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a zwitterion functionalized cyclodextrin sulfonated polymer proton exchange membrane, characterized in that: The following steps are involved: (1) N-aminoethylpiperazine (AEP) and a first solvent are placed in a container together, and then a mixture of 1,3-propyl sultone (1,3-PS) and a second solvent is added dropwise to the container under a water bath condition of 20° C. to 50° C., and the mixture is stirred for reaction, and then the product is separated, washed, and dried to obtain a corresponding zwitterionic compound, which is recorded as AEPPS; (2) stirring the AEPPS obtained in step (1) together with NaOH, β-cyclodextrin (β-CD) and deionized water in an oil bath at 60° C. to 100° C., and simultaneously adding epichlorohydrin (ECH) dropwise thereto to obtain a mixed solution, connecting a reflux condenser to perform a heating reflux reaction, and then separating, washing and drying the product to obtain the corresponding zwitterionic compound-modified cyclodextrin, denoted as ZCD; (3) dispersing the ZCD obtained in step (2) in a sulfonated polymer solution, and ultrasonically treating the solution to obtain a uniformly dispersed casting solution; then, using the casting solution to form a membrane material, drying the membrane material, and then sequentially soaking the membrane material in a hydrogen peroxide solution, an acid, and deionized water to obtain a zwitterion-functionalized cyclodextrin sulfonated polymer proton exchange membrane.
2. The preparation method according to claim 1, characterized in that: In step (2), the dropwise addition volume of epichlorohydrin accounts for 5 to 20% of the total volume of the mixed solution; the reaction temperature of the reflux heating reaction is 60 to 80° C., and the reaction time is 15 to 180 min; Preferably, the dropwise added volume of epichlorohydrin accounts for 5-12% of the total volume of the mixed solution; the reaction temperature of the reflux heating reaction is 65-80° C., and the reaction time is 15-150 min.
3. The preparation method according to claim 1, characterized in that: In step (3), the mass of ZCD accounts for 0.7-2.1 wt % of the mass of the polymer matrix contained in the sulfonated polymer solution.
4. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the N-aminoethylpiperazine to the 1,3-propyl sultone corresponding to the stirring reaction is 5:1 to 1:
5.
5. The preparation method according to claim 1, characterized in that: In step (1), the first solvent and the second solvent are independently selected from one or a mixture of N,N-dimethylformamide (DMF), acetonitrile, N,N-diethylformamide, tetrahydrofuran, pyrrolidone, dimethyl sulfoxide, CH3OH, C2H5OH; The temperature of the water bath condition is 25-45° C.; the reaction time of the stirring reaction is 2-12 hours.
6. The preparation method according to claim 1, characterized in that: In step (1) and step (2), the solvents used for cleaning are all low-boiling point solvents with a boiling point not higher than 80° C., independently selected from one or a mixture of CH3OH, C2H5OH, CHCl3, CH2Cl2, CH3Cl, acetone, and butanone.
7. The preparation method according to claim 1, characterized in that: In step (3), the sulfonated polymer solution is a homogeneous solution of perfluorosulfonic acid resin, sulfonated polyetheretherketone, sulfonated polybenzimidazole, sulfonated polyethersulfone or sulfonated polyimide; the concentration of the sulfonated polymer solution is 1 to 40 wt%; Using the casting liquid to form a membrane material, specifically coating the casting liquid to form a membrane; The drying is to place the membrane material in a 50-80°C oven, heat it to 110-150°C, and then keep it for 12-36 hours; preferably, the heating rate of the heating is less than 0.5°C / min, more preferably 0.1-0.5°C / min.
8. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the hydrogen peroxide solution is 1 to 10 wt %; The acid solution is specifically one or a mixture of hydrochloric acid, sulfuric acid, phosphoric acid, and the concentration of the acid solution is 0.1 to 2 mol / L, more preferably 0.5 to 2 mol / L.
9. A zwitterion-functionalized cyclodextrin sulfonated polymer proton exchange membrane prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the zwitterion-functionalized cyclodextrin sulfonated polymer proton exchange membrane as claimed in claim 9 in a proton exchange membrane fuel cell.
Citation Information
Patent Citations
Polymer hybrid proton exchange membrane synergistically modified by zwitter-ion functionalized COF and SiO2 spheres
CN117380003A
Composite proton exchange membrane for methanol fuel cell and preparation method of composite proton exchange membrane
CN102945977A
Graphene oxide composite membrane with pH responsiveness as well as preparation method and application of graphene oxide composite membrane
CN116422155A
Fall prevention device for steel tower
KR1020240158679A
Ion exchange composite material based on proton conductive functionalized inorganic support compounds in a polymer matrix
US20050053818A1